2007
DOI: 10.1002/art.23011
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a rehabilitation program integrating exercise, self‐management, and active coping strategies for chronic knee pain

Abstract: Objective. To conduct an economic evaluation of the Enabling Self-Management and Coping with Arthritic Knee Pain through Exercise (ESCAPE-knee pain) program. Methods. Alongside a clinical trial, we estimated the costs of usual primary care and participation in ESCAPE-knee pain delivered to individuals (Indiv-rehab) or groups of 8 participants (Grp-rehab). Information on resource use and informal care received was collected during face-to-face interviews. Cost-effectiveness and cost-utility were assessed from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 33 publications
(37 reference statements)
1
112
1
1
Order By: Relevance
“…[29][30][31][32] It should be noted that one study found exercise interventions were effective for functional improvements compared with 'usual care'. 19 However, greater gains in quality-of-life measures were found in the 'usual care' group than in the 'exercise' intervention groups (negative cost per QALY), so the cost per QALY was difficult to interpret. 19 Comparing the annual cost per participant to become active is difficult due to the different definitions and analytical approaches used.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…[29][30][31][32] It should be noted that one study found exercise interventions were effective for functional improvements compared with 'usual care'. 19 However, greater gains in quality-of-life measures were found in the 'usual care' group than in the 'exercise' intervention groups (negative cost per QALY), so the cost per QALY was difficult to interpret. 19 Comparing the annual cost per participant to become active is difficult due to the different definitions and analytical approaches used.…”
Section: Qaly = Quality-adjusted Life-yearmentioning
confidence: 99%
“…123,124 Data from the cohort study indicated that many patients only consult their GP about their condition once within a period of 3 years. Patients consulting their GP were likely to be initially offered advice and pain medication(s) according to the severity of their symptoms and, thereafter, stronger pain medications, referral for physiotherapy and eventually surgery as the last treatment option if the pain persisted.…”
Section: Current Carementioning
confidence: 99%
“…Owing to the lack of detailed data on health-care resource use in the cohort, the costs of current care were considered to be as reported in the control arm (current GP-led care) in a trial of exercise in knee OA patients. 123,124 Treatments included advice, exercise and pain medication(s) including simple analgesia (paracetamol and aspirin), topical and oral NSAIDs, and opioids. Table 3 contains information on the baseline proportion of patients in each health state at baseline and provides estimates for the clinical effectiveness of individual treatments.…”
Section: Current Carementioning
confidence: 99%
See 2 more Smart Citations